1991
DOI: 10.1128/aac.35.11.2345
|View full text |Cite
|
Sign up to set email alerts
|

Temafloxacin pharmacokinetics in subjects with normal and impaired renal function

Abstract: The pharmacokinetics of temafloxacin were investigated following oral administration of single 400-mg doses to 6 normal subjects and 18 subjects with various degrees of impaired renal function. Renal impairment did not significantly affect the peak concentration, time to peak concentration, or the nonrenal clearance of temafloxacin. Both renal clearance (CLR) and total apparent clearance (CLT/F, where F represents the fraction of dose absorbed) of temafloxacin were highly correlated with creatinine clearance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These include fluoroquinolones that predominantly use renal elimination pathways (e.g., levofloxacin, ciprofloxacin, temafloxacin, and clinafloxacin) and those that favor non-renal elimination pathways (e.g., sparfloxacin eliminated via glucuronide metabolism, biliary excretion, and possibly intestinal secretion) [18][19][20][21][22] . Our results are similar to those reported for moxifloxacin in that no dosage adjustment is indicated in subjects with renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…These include fluoroquinolones that predominantly use renal elimination pathways (e.g., levofloxacin, ciprofloxacin, temafloxacin, and clinafloxacin) and those that favor non-renal elimination pathways (e.g., sparfloxacin eliminated via glucuronide metabolism, biliary excretion, and possibly intestinal secretion) [18][19][20][21][22] . Our results are similar to those reported for moxifloxacin in that no dosage adjustment is indicated in subjects with renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Some quinolone antibacterial drugs such as ciprofloxacin and temafloxacin are known to be eliminated from the gastrointestinal tract in humans (Granneman et al, 1991;Sör-gel et al, 1989bSör-gel et al, , 1991. We previously reported that gastrointestinal secretion of grepafloxacin and levofloxacin was mediated by P-glycoprotein and another transport system distinct from organic cation and anion transporters in Caco-2 cells (Yamaguchi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The intestine has been shown to play an important role as an elimination tissue or absorption barrier. It was reported that at least 10.6% of intravenously administered ciprofloxacin was eliminated by intestinal secretion (Sörgel et al, 1989b(Sörgel et al, , 1991, and temafloxacin showed significant gastrointestinal secretion into feces in humans (Granneman et al, 1991). Dautrey et al (1999) suggested that the pharmacokinetics of ciprofloxacin involved one or more active secretory mechanisms in the intestine in rats.…”
mentioning
confidence: 99%
“…The new fluoroquinolones sparfloxacin and temafloxacin show greater lethal rates than nor floxacin and ciprofloxacin, though killing ki netics are slower and not as great as those de tected in the case of gram-negative bacteria [19,20,22,23] (however it must be stressed here that temafloxacin has been withdrawn from clinical use after the experimental part of this work was performed). On the other hand, the paradoxical effect shown by quinolones has no relevance in systemic infections, as clinically achievable quinolone levels in se rum and tissues are currently within the OBC [17,18,[24][25][26], but they could have implica tions in the treatment of urinary-tract infec tions because quinolone concentrations in urine are higher than their respective OBCs [7,14,20,23,27], and are thus less effective at killing bacteria. Tenney et al [28], by repeated exposure of bacteria to subinhibitory concen trations of ciprofloxacin and norfloxacin, rap idly produced isolates with MICs up to 512-fold higher than the original strain, so, high drug concentrations, being less bactericidal, may behave similarly to subinhibitory concen trations and could produce isolates with higher MICs.…”
Section: Discussionmentioning
confidence: 99%